Insulinoma; a diagnostic challenge: a case report - Wania Rafaey; Asim Munir Alvi; Sidra Aslam; Ahmed Imran Siddiqui; Waqas Shafiq (Journal of the Pakistan Medical Association)
Insulinoma is a pancreatic neuroendocrine tumour that primarily leads to episodes of hypoglycaemia due to inappropriate and excessive secretion of insulin. It classically presents with neuroglycopenic and autonomic sympathetic symptoms, which resolve promptly with glucose administration. Elevated level of insulin and C-peptide in the presence of low plasma glucose level and absence of plasma sulfonylurea are diagnostic features. Localisation of the tumour is essential before surgery. However, Insulinoma is difficult to diagnose due to its ambiguous location and insidious course. This is the case of a young male who had 6 months history of adrenergic and neuroglycopenic symptoms, including one episode of seizure. His symptoms resolved with the consumption of high glycaemic indexed food. Biochemical tests were suggestive of insulinoma, but non-invasive imaging techniques including computer tomography (CT) and magnetic resonance imaging (MRI) could not localise the tumour. In this case, pancreatic insulinoma was localised by endoscopic pancreatic ultrasound (EUS). He underwent successful resection of the tumour and his symptoms resolved completely post-surgery.